Genetically and dietary induced obesity associate differently with gut microbiota in a murine intestinal tumorigenesis model - Knut Rudi; Jane Ludvigsen; Hubert Dirven; Inger-Lise Steffensen (Wolters Kluwer Medknow Publications, 2017)
Background: Overweight and obesity are risk factors for human colorectal cancer. Growing evidence suggests that the gut microbiome affects both obesity and cancer. In this study, we examined how the murine microbiota composition correlated with obesity, intestinal tumorigenesis, glucose regulation, and inflammation. Materials and Methods: We used 16S ribosomal RNA gene analyses of feces and data obtained from a double-mutant mouse model; multiple intestinal neoplasia (Min), mice, which spontaneously develop intestinal tumors, crossed with obesity (ob), mice, which develop obesity, fed 10% or 45% fat diet. Results: We found that diet and genotypes imposed a major impact on the gut microbiota composition. Likewise, we found strong associations of the microbiota composition with obesity, number of small intestinal tumors, and blood glucose levels. Specifically, bacteria related to Clostridium perfringens and Lactobacillus showed strong positive associations with both dietary induced and genetically induced obesity, while Bacteroidales showed strong negative associations. Representatives of Lachnospiraceae and Peptostreptococcaceae only showed significant negative associations with genetically induced obesity and no associations with dietary induced obesity. Conclusions: We found complex associations between the microbiota and genetic background, diet, obesity, glucose levels, inflammation, and intestinal tumorigenesis. This could contribute to the lack of consensus between the results in previous studies regarding correlations of microbiota with obesity and cancer.